Ambientes agrícolas e adubação organo e/ ou mineral no desempenho agronômico da cultura do morango no litoral cearense - Chagas, Keivia Lino (2017)
In the Brazilian Northeast, the cultivation of strawberry has reached its value in the Market, however, this production is still small to supply the demand, due adverse climatic conditions. Acclimatized environments can approach to the local conditions observed in the producing regions in Brazil. Another factor is the elevated use of mineral inputs in strawberry faming, which can be reduced with use of organic fertilization. This work was designed with the objective of evaluate the effect of organic fertilization and/or mineral under cultivated strawberry in different environments in the seacoast of Ceará. The field experiment was executed in the area of Federal University of Ceará, at the Pici Campus, Fortaleza, Ceará. The trial design utilized was disposed in a complete randomized block in split-spot, within four repetitions, combining the three growing environments denominated: A1, a protected environment of acclimatized type; A2, open sunlight, with no sort of solar protection, and A3, environment covered by shade cloth with efficiency of 70%. The subplots were composed with six types of fertilization: T1, mineral input (50%° + biofertilizer of goat manure (50%); T2, mineral (50%) + biofertilizer of cattle manure (50%), T3 cattle manure (100%); T4, goat manure (100%); T5, mineral (100%); T6 control. The experimental unity was formed with two pots, with two plants each, and with four blocs, totalizing 48 pots by cultivated environment and 192 in the total of the experiment. It was analyzed variables from biomass (dry matter from the leaves, stem and root), from production (average mass of fruit, number of fruits and productivity) and from post-crop (length and diameter of fruit and content of soluble solids). The collected data to each variable, referring to the environments and fertilizations, were submitted to the analysis of variance. For all the studied variables, the greater values occurred when organic-mineral fertilization with cultivation in acclimatized environment was performed. In opposition, the lowest values were observed when there was no fertilization under open sunlight.